Measurement of Efficient Travel Time of a Highway Corridor Through Moving Observer Method: A Case Study on Savar-Manikganj Highway in Bangladesh - Hasan, Md Abir; Fahim, Ashraf Uddin (Journal of Engineering Science, 2022)
Travel time and its variability is one of the biggest controlling factors for trip planning, mode selection and forecasting trip duration. Travel time can be affected by various issues. Savar-Aricha highway is the gateway between south and south-western part of the country. Large variability on this corridor can cause great economic losses. To understand this routes travel time, running velocity and level of service moving observer method was conducted. The survey also includes travel time, stopped time and journey time for two types of public transport present on the corridor: ticket-based bus system and without ticket local bus system. The study found that, Ticket based bus system has lesser travel time and stopped time resulting is less travel time in comparison with local bus system. Speed analysis for both the route also supports this. In consideration of free flow speed, the level of service of this corridor was found A. Journal of Engineering Science 13(1), 2022, 21-29